Fillerless TIG Welding Application for Weld Repair of Tube Joint between Dissimilar Stainless Steel - Ruksut, Chanerin; Kanchana, Rapee; Kimapong, Kittipong; Chantasri, Sakchai (Journal of Advanced Development in Engineering and Science, 2023)
This research aimed to apply a tungsten inert gas welding (TIG welding) for welding a seamless tube butt joint between dissimilar AISI304 and AISI316L stainless steel with one pass welding and multi-pass welding. The butt joint of 3 types was designed and was welded using a welding current of 135 A, Ar gas flow rate of 12.5 l/min, and a welding speed of 200 mm/min. The welded specimens were prepared and investigated for a relative of a joint property and metallurgical characteristic. The summarized results were as follows. TIG welding could successfully produce a multi-pass welding of dissimilar AISI304 and AISI316L stainless steel butt joint as expectation. When an AISI304 stainless steel component was higher in the weld metal, an increase of a weld width, an increase of a weld concave, and a decrease of a root convex could be observed. When compared a tensile strength of the welded joint, it found that a tensile strength of the multi-pass welded joint was 20-30% lower than that of the one pass welded joint. The multi-pass welded joint that composed larger amount of AISI304 stainless steel composition produced higher tensile strength and narrower weld area than that of AISI304 stainless steel.